Beyond colors: The health benefits of maize anthocyanins - Bharat Bhushan; Satish Kumar; Charanjeet Kaur; Veena Devi; Dharam Paul Chaudhary; Alla Singh; Manesh Chander Dagla; Chikkappa Gangadhar Karjagi; Lejaniya Abdul Kalam Saleena; Deepak Chandran; Manoj Kumar (Applied Food Research, 2024)
The anthocyanins (ACN) are watersoluble pigments present in the pericarp or aleurone layer of maize kernel. The authentic color landraces being grown by the farmers at a smaller scale restricted to local consumers. These color ears (cob with color kernels) which are receiving more prominence not only for their environment friendly and natural colorant properties but also to their numerous health benefits from edible food pigments. Since anthocyanin pigments have significant effects on animal health, it is also catching the attention of food processing companies as well as highend culinary markets. In this review, we have represented functional properties of anthocyanins present in maize. Earlier, studies best on in vitro tests were extrapolatory but now using cell models and animal trials are providing foolproof evidence for functional significance of corn anthocyanins. The mechanisms of action at the cellular and molecular level have been understood.